STATISTICAL STUDY OF INTERACTIONS BETWEEN FOREIGN TRADE AND ECONOMIC GROWTH FOREIGN EXPERIENCE - N.I.Hayitova - TFI (Scholar Express Journals, 2023)
This article delves into a statistical investigation of the relationship between foreign trade and economic growth, drawing insights from global experiences. By utilizing advanced statistical methods, the aim is to shed light on how foreign trade interacts with economic growth in different countries and contexts
Keywords: Foreign trade; Economic growth; Interactions